Interoperable Health Data Architecture: Enabling Seamless Patient Engagement Across Multi-Platform Systems - Vinjamuri, Jagdish Kumar (Journal of Neonatal Surgery, 2021)
- The healthcare sector's rapid digital modernization is creating an insatiable demand for health data architectures designed to enable interoperable health data. An interoperable health data architecture can connect interoperable systems and platforms, disseminate data among different constituents of health data, and improve patient engagement via different digital channels, such as electronic health records (EHRs), from cloud-based applications to mobile health apps and wearables, and telehealth. This paper has described how the design, development, and evaluation of an interoperable health data architecture can facilitate patient engagement. The benefits of using health data exchanges based on data exchange formats, protocols, and/or APIs like HL7 FHIR and open APIs are also described to allow real-time use and synchronization of patient data as patients and healthcare professionals share and exchange data with health data exchanges. In addition, the importance of privacy-preserving sharing of data, data governance, and collaborative or user-centred design and development are described to build trust and increase or improve the adoption and use of common data exchange products utilised by patients and healthcare professionals. In summary, the proposed interoperable health data architecture is a step towards a unified and patient data accessible ecosystem, improving continuity of care, informed decision-making, and fostering an informed and engaged patient, as well as showing the protocols linking to proposed best practices and the key challenges that must be overcome for scalable and sustainable interoperability in a fragmented digital landscape of health care